Social Inquiry Learning Model in Improving Elementary School Students' Critical Thinking Skills - Bahtiar, Reza Syehma; Desiningrum, Noviana; Putri, Ellena Aurellia (Universitas Nahdatul Ulama Surabaya, 2024)
The importance of developing critical thinking skills in elementary education has gained increasing recognition, particularly through the implementation of inquiry-based learning (IBL) models. This study aims to evaluate the effectiveness of the social inquiry learning model in enhancing critical thinking skills among fourth-grade students at an public elementary school in Surabaya. Employing a qualitative case study methodology, data were collected through interviews, classroom observations, reflective journals, and document analysis. The thematic analysis revealed significant improvements in critical thinking for 75% of the participants, highlighting key themes such as